The potential of the snail hawk as a biological controller of the apple snail in rice crops (Revista Científica Ciencias Naturales y Ambientales, 2023)
There are many ways to control apple slugs, which highlights the important role of the Snail Sparrowhawk in maintaining ecosystems as a natural predator, since 95% of the bird’s diet consists of freshwater snails of the genus Pomacea. The main objective of this study was to determine the potential of the sparrowhawk (Rostrhamus sociabilis) as a biological control agent of the apple slug (Pomacea canaliculata) in rice crops in Luhr-Port Manavi. This study uses the analytical method, the inductive method and the field survey method and consists of three stages and methods: survey and observation. In the first stage, situational diagnosis was used to analyze the rice production process in the 25 identified plots. In the second stage, the feeding behavior of the slug eagle was determined. With two specimens, females and males, 53 and 59 feeding cycles were recorded, respectively, as a reference. These cycles consisted of four categories: foraging, processing prey in flight, processing prey at rest and searching for the next meal. Finally, the potential of the study bird as a biocontrol agent was determined by monitoring its feeding, yielding results of a consumption density of 184 snails/week*ha and a potential 88.04% above the potential of Alamos. 11.96%), which indicates that the hawksbill snail has a great potential as a biological control of the apple snail.
Keywords: Rice; Food; Poutry; Pests